Identification of Entamoeba histolytica by Molecular Method in Surface Water of Rasht City, Iran - Arash Hemmati; Elham Hooshmand; Mohammad Javad Hosseini (Tehran University of Medical Sciences, 2015)
Background: This study was conducted with the aim of determining surface water contamination with cysts of Entamoeba histolytica using PCR in Rasht City, Northern Iran. Methods: In this cross-sectional study, 49 water samples including 18 rivers and 6 wetlands were collected from different regions near the city of Rasht in autumn of 2012. After filtration using 0.22 µm nitrate cellulose membrane filters, the samples were examined using microscope and PCR method. Results: In microscopic examination, four samples of the 49 samples were positive for cysts of E. (histolytica / dispar / muschkovskii). By using PCR method and molecular analysis, one sample was positive for E. histolytica. Conclusion: In the molecular analysis, contamination by E. histolytica was proved in the waters of Rasht City. Further investigations including more samples and necessary preparations must be applied to prevent contamination.